Morphology of natural rubber latex particles prevulcanised by sulphur and peroxide systems - Pramuan Tangboriboonrat (2018)
Transmission electron microscopy provided direct evidence of the morphology of sulphur- and peroxide-prevulcanised natural rubber latex particles. A mesh structure of all cross-linked rubber particles containing polystyrene, prepared using the phase-transfer/bulk polymerisation process, was found. Each peroxide-prevulcanised particle had a nonuniform network structure, whereas the rubber network in sulphur-prevulcanised particles was homogeneous, irrespective of size. The effects of maturation and sodium dodecyl sulphate on the swelling ratio of the sulphur-prevulcanised latex film were investigated.